Bioinorganic chemistry : inorganic elements in the chemistry of life : an introduction and guide - Kaim, Wolfgang, 1951-; Schwederski, Brigitte, 1959-; Klein, Axel, 1964- (Chichester, West Sussex, United Kingdom : John Wiley & Sons Inc., 2013)
'Completely revised and updated with new topical material, the second edition of Bioinorganic Chemistry summarizes in one comprehensive volume the current knowledge on the role of inorganic elements in biological processes and their application as biological agents. Now in full color, each chapter has been fully revised and updated to take account of the latest developments. An important reference for researchers and students, this classic text features new material on: neurotransmitter gases, life under extreme conditions, materials aspect of bioinorganic chemistry, elemental cycles, bioorganometallic chemistry, imaging with bioinorganic substances, and therapeutic advances'--
Translation of: Bioanorganische Chemie.
Buku Bacaan Asas Fakulti
Includes bibliographical references and index.
Buku bacaan asas fakulti
Keywords: Bioinorganic chemistry